"I can, therefore I must": Fragility in the upper-middle classes. (17th December 2013) - Luthar, Suniya S.; Barkin, Samuel H.; Crossman, Elizabeth J.
Abstract: We review evidence on a group recently identified as "at risk, " that is, youth in upwardly mobile, upper-middle class community contexts. These youngsters are statistically more likely than normative samples to show serious disturbance across several domains including drug and alcohol use, as well as internalizing and externalizing problems. Extant data on these problems are reviewed with attention to gender-specific patterns, presenting quantitative developmental research findings along with relevant evidence across other disciplines. In considering possible reasons for elevated maladjustment, we appraise multiple pathways, including aspects of family dynamics, peer norms, pressures at schools, and policies in higher education. All of these pathways are considered within the context of broad, exosystemic mores: the pervasive emphasis, in contemporary American culture, on maximizing personal status, and how this can threaten the well-being of individuals and of communities. We then discuss issues that warrant attention in future research. The paper concludes with suggestions for interventions at multiple levels, targeting youth, parents, educators, as well as policymakers, toward reducing pressures and maximizing positive adaptation among "privileged but pressured" youth and their families.